2004
DOI: 10.1021/la0499259
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Poly(styrene/α-tert-butoxy-ω- vinyl-benzyl-polyglycidol) Microspheres on Mica Plates Crossing the Liquid−Air Interface:  Formation of Stripe Pattern

Abstract: Formation of stripelike assemblies of poly(styrene/alpha-tert-butoxy-omega-vinyl-benzyl-polyglycidol) microspheres adsorbed on nonpatterned mica plates moving perpendicularly from suspension of particles through the water-air interface has been observed. It was found that ordered assemblies were formed by capillary forces acting on particles crossing the water-air boundary. At sufficiently high rates of plate movement (i.e., at appropriate dynamic loading conditions) the adsorbed microspheres approaching the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Przerwa et al conducted the dip coating using the negatively charged polymer latex and the amine-modified mica substrate and obtained the colloidal layers with the structure similar to those of the PAPTAC-Si monolayers shown in Fig. 5c, d [35]. Ray et al also reported the similar wiggle bead structure prepared by the drying process of the positively charged colloidal suspension on the negatively charged glass substrate [36].…”
Section: Mica Substrate (Fixed)mentioning
confidence: 89%
“…Przerwa et al conducted the dip coating using the negatively charged polymer latex and the amine-modified mica substrate and obtained the colloidal layers with the structure similar to those of the PAPTAC-Si monolayers shown in Fig. 5c, d [35]. Ray et al also reported the similar wiggle bead structure prepared by the drying process of the positively charged colloidal suspension on the negatively charged glass substrate [36].…”
Section: Mica Substrate (Fixed)mentioning
confidence: 89%
“…In fact, the MCED rates in the present study are still so low for dynamic scanning-mode that the scanning rate has a negligible effect on the meniscus shape, as predicted by static mechanics . Based on mass balance of the solvent/particle mixture, at steady state, the flow rate of solvent leaving the meniscus by evaporation equals that of solvent molecules entering the meniscus from the pipet.…”
mentioning
confidence: 87%
“…In fact, the MCED rates in the present study are still so low for dynamic scanning-mode that the scanning rate has a negligible effect on the meniscus shape, as predicted by static mechanics. 30 Based on mass balance of the solvent/particle mixture, at steady state, the flow rate of solvent leaving the meniscus by evaporation equals that of solvent molecules entering the meniscus from the pipet. Assuming negligible diffusion of copper ions at x = −R in Figure 1c, the mass conservation yields C 0 l ev j ̃ev = ρ s hυ̃c, where the total evaporation flux is defined by Q ev = ∫ 0 l ev j ev (x) dx with a mean evaporation rate j ̃ev = Q ev /l ev per unite length over the evaporation region of length l ev for a bulk copper mass concentration of C 0.…”
mentioning
confidence: 99%
“…46 When substrates with a charge opposite to that of the particles are used, that is, there exists electrostatic attraction between a substrate and particles, a mechanism different from the stick-slip phenomenon seems to work in the formation of stripelike patterns by using the convective assembly method. Przerwa et al suggest that the formation of particle aggregates is strongly affected by the shape of the meniscus in the vicinity of the substrate surface, 47 and Ray et al successfully calculated stripe spacing assuming a wedge-shaped liquid film around the tip of the meniscus. 48 However, the stripe patterns formed in this process are not well-defined because the strong adhesive force between the substrate and the particles hinders the rearrangement of particles on the substrate.…”
Section: Introductionmentioning
confidence: 99%